Application of Patient Reported Outcomes Measurement Information System (PROMIS) in Elite Athletes. Issue 3 (14th September 2018) - Hunt, Kenneth; Lakey, Eric; Roberts, Jesse; Kumparatana, Pam
Category: Sports Introduction/Purpose: Since its introduction into clinical practice, the Patient-Reported Outcome Measurement Information System (PROMIS) has become commonplace across multiple different orthopaedic sub-specialties for a wide variety of patient populations. PROMIS computer adaptive tests (CATs) are increasingly administered following injury and/or surgical intervention. Yet, a gap in the literature remains with regard to the results of PROMIS scores in populations that may not conform to mean normal values in the NIH PROMIS scoring database. Examples include young, healthy patients and young, elite athletes. Our objective was to evaluate the performance of scoring tools in six PROMIS domains in young, healthy non-athlete individuals and young, uninjured elite athletes, comparing both to National Institute of Health (NIH) developed normal PROMIS means and Standard deviations. Methods: In an IRB approved prospective cohort study, healthy subjects were recruited from a large University with a National Collegiate Athletic Association (NCAA) Division 1 athletics program between May and November 2017. Subjects were administered a one-time survey, including the following six PROMIS domains: Pain Interference CAT, Physical Functioning CAT, Mobility CAT, Social Functioning CAT, Depression CAT, and Global Health Short Form. Demographics included age, gender, sport and level of participation (where applicable), self-reported health status, history of recent orthopaedic injury, and history of foot/ankle surgery. Elite athletes were defined as participants > 18 years old actively participating in NCAA Division 1 athletics. Young people were defined as non-NCAA Division 1 athletes ages 18 to 35 years old. Following completion of data collection, results were analyzed using SAS 9.4. Results: The final cohort consisted of a total of 206 participants, which included 39 elite athletes, and 167 healthy non-athletes. All six PROMIS domains demonstrated statistically significant differences (p-value < 0.01) comparing elite athletes to NIH normal values. Compared to healthy non-athletes, elite athletes' scores were all significant different (p-value < 0.01) except for the PROMIS Social Functioning CAT (p = 0.0766) and PROMIS Global Health Short Form Physical Functioning T-score (p = 0.0916). Furthermore, when elite athletes were compared to similar age undergraduates students (n = 25) only PROMIS Depression CAT and Global Health Short Form Mental Health T-score were statistically significant (p-value < 0.01). Conclusion: Elite athletes' baseline PROMIS scores are significantly different than both the NIH normal values, and young healthy non-athletes across PROMIS domains. This highlights the need to interpret the results of elite athletes' scores in the context of normal values for this specific population, and taking this into account over the of course of care following injury and/or surgery. There is a need for further research to establish baseline normal values for PROMIS scores for elite athletes and other populations of specific interest to the orthopaedic foot and ankle surgeon, to ensure proper interpretation of scores throughout the course of treatment.